A human nuclear uracil DNA glycosylase is the 37-kDa subunit of glyceraldehyde-3-phosphate dehydrogenase. - Meyer-Siegler, K (1991)
We have isolated and characterized a plasmid (pChug 20.1) that contains the cDNA of a nuclear uracil DNA glycosylase (UDG) gene isolated from normal human placenta. This cDNA directed the synthesis of a fusion protein (Mr 66,000) that exhibited UDG activity. The enzymatic activity was specific for a uracil-containing polynucleotide substrate and was inhibited by a glycosylase antibody or a beta-galactosidase antibody. Sequence analysis demonstrated an open reading frame that encoded a protein of 335 amino acids of calculated Mr 36,050 and pI 8.7, corresponding to the Mr 37,000 and pI 8.1 of purified human placental UDG. No homology was seen between this cDNA and the UDG of herpes simplex virus, Escherichia coli, and yeast; nor was there homology with the putative human mitochondrial UDG cDNA or with a second human nuclear UDG cDNA. Surprisingly, a search of the GenBank data base revealed that the cDNA of UDG was completely homologous with the 37-kDa subunit of human glyceraldehyde-3-phosphate dehydrogenase. Human erythrocyte glyceraldehyde-3-phosphate dehydrogenase was obtained commercially in its tetrameric form. A 37-kDa subunit was isolated from it and shown to possess UDG activity equivalent to that seen for the purified human placental UDG. The multiple functions of this 37-kDa protein as here and previously reported indicate that it possesses a series of activities, depending on its oligomeric state. Accordingly, mutation(s) in the gene of this multifunctional protein may conceivably result in the diverse cellular phenotypes of Bloom syndrome.